Xp11.22 Microduplications Including HUWE1: Case Report and Literature Review - Orivoli, Sonia; Pavlidis, Elena; Cantalupo, Gaetano; Pezzella, Marianna; Zara, Federico; Garavelli, Livia; Pisani, Francesco; Piccolo, Benedetta (Neuropediatrics, 2016)
Xp11.22 microduplications have been reported in different patients with X-linked intellectual disability. Comparing the duplicated segments, a minimum region of overlap has been identified. Within this region, only one gene, the HUWE1 gene, coding the E3 ubiquitin protein ligase, turned out to be duplicated in all previously described patients. We provide a review of the literature on this topic, making a comparison not only of genetic aspects, but also of clinical, neurophysiological, and neuroradiological findings. Furthermore, we describe the phenotypic and molecular characterization of a case of intellectual disability in a child carrying one of the smallest Xp11.22 microduplications reported, involving the whole sequence of HUWE1 gene. Unlike previously described cases, our patient's neuroimaging showed abnormal findings; he also experienced one seizure and showed interictal electroencephalogram (EEG) epileptiform abnormalities. Given the fact that HUWE1 duplications and mutations have previously been described in several patients with X-linked cognitive impairment, our findings support the hypothesis that HUWE1 gene might be implicate in the pathogenesis of intellectual disability. Nevertheless, further investigations and a more detailed examination of patients' clinical history are needed to clear up other eventual genotype–phenotype correlations, such as the presence of epilepsy/epileptiform EEG abnormalities.
Keywords: intellectual disability; HUWE1; X-linked; EEG abnormalities